The Impact of Equity Financing on Financial Performance: Evidence from Jordan - Almanaseer Sufian (Foundations of Management)
The main objective of this study is to examine the impact of equity financing on the financial performance of Jordanian industrial companies. The study population comprised 393 board directors from 55 Jordanian industrial companies. Purposive sampling was employed to select 346 board directors for the study sample. Data were collected via an online questionnaire, and the study used a descriptive-analytical approach to examine the study hypotheses. The study concludes that equity financing posi-tively impacts financial performance. Also, each of the angel investors, retained earnings, crowdfunding, and ploughed-back profit positively impact financial performance. The study recommends that Jordanian industrial companies focus on retained earnings as a funding source; what helps is the lower costs of obtaining financing from retained earnings compared with other funding sources. This study is unique because, as far as the researcher knows, it is the first to look at how angel investors, retained earnings, crowdfunding, and ploughed-back profit affect the financial performance of Jordanian industrial compa-nies all at the same time or separately.